Pemanfaatan By Product Pengolahan Ekstrak Albumin Ikan Gabus Menjadi Abon Ikan Di LPM Kelurahan Sekumpul - Dewi Kartika Sari; Rita Khairina; Karenina Mursida; Dita Amalia Mahmudah (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
The by-product of processing snakehead fish albumin extract is obtained in the form of fish meat with a tasteless taste because the fish juice has been separated in the form of albumin extract. The by product can still be used as other processed products, by adding a mixture of spices to obtain a product, namely shredded fish. The objectives of this service activity are (1) to increase the added value of by product processing snakehead fish albumin extract into a selling value product, namely shredded fish and (2) as an effort to accelerate community empowerment in an area by utilizing local potential in the area. The method of PKM activities at LPM Kelurahan Sekumpul uses counseling, training, demonstration and evaluation techniques of service activities. The conclusions of this service activity, namely (1) the processing of shredded fish is an effort to optimize the utilization of by-product processing of snakehead fish albumin extract into products that have economic value; (2) shredded fish made from snakehead fish albumin can be an option to increase fish consumption in an effort to meet the nutritional adequacy of the community, especially the fulfillment of animal protein sources; (3) the results of the evaluation of the level of understanding of the target audience on the criteria of understanding and practicing the service material increased by 46.7%, then on the criteria of understanding and not practicing it decreased by 26.6% and on the criterion of understanding slightly decreased by 20%.